Immune neonatal thrombocytopenia - review - Sequeira,Ana Isabel (2020)
Introduction: Thrombocytopenia is the most frequent hematological change in the neonatal period, with immune thrombocytopenia as the main cause of moderate-to-severe thrombocytopenia in apparently healthy newborns. Immune thrombocytopenia in the fetus or newborn may result from platelet alloantibodies against paternal antigens inherited by the fetus (alloimmune thrombocytopenia) or platelet autoantibodies due to maternal autoimmune disease (autoimmune thrombocytopenia). Objetives: To review published literature about immune thrombocytopenia in newborns, including the latest advances in pathogenesis, diagnosis, treatment, and prevention. Results: Neonatal alloimmune thrombocytopenia is the most common cause of severe thrombocytopenia and intracranial hemorrhage in term neonates. Clinical presentation varies from mild thrombocytopenia to life-threatening bleeding and death. As maternal screening is not routinely performed, most cases are diagnosed in the first child. Despite intensive research, a consensus strategy for prevention and treatment of the condition is lacking. Diagnosis of neonatal autoimmune thrombocytopenia is usually apparent from maternal medical history and thrombocytopenia. Although maternal immune thrombocytopenic purpura does not carry a high risk of perinatal hemorrhage, it may lead to thrombocytopenia in the newborn, mostly mild-to-moderate. Clinical presentation varies from no symptoms to mucocutaneous signs of thrombocytopenia and may persist for weeks to months requiring long-term monitoring. Conclusions: Fetal and Neonatal alloimmune thrombocytopenia can cause severe disease in the affected fetus or newborn. Facing the lack of routine antenatal screening, the strategies currently proposed for pregnancies at risk. We also discussed the latest research and therapies in development, aiming at potential improvements in diagnosis, treatment, and prevention of this disease. Neonatal autoimmune thrombocytopenia may cause long-lasting low platelet count, that need regular checking.